Sediment storage and shallow groundwater response to beaver dam analogues in the Colorado Front Range, USA. (28th January 2020) - Scamardo, Julianne; Wohl, Ellen
Abstract: Enthusiasm for using beaver dam analogues (BDAs) to restore incised channels and riparian corridors has been increasing. BDAs are expected to create a similar channel response to natural beaver dams by causing channel bed aggradation and overbank flow, which subsequently raise water tables and support vegetation growth. However, lack of funding for monitoring projects post‐restoration has limited research on whether BDAs actually cause expected channel change in the Front Range and elsewhere. Geomorphic and hydrologic response to BDAs was monitored in two watersheds 1 year post‐restoration. BDAs were studied at Fish Creek, a steep mountainous catchment, and Campbell Creek, a lower gradient piedmont catchment from May to October 2018. At each restoration site, the upstream‐ and downstream‐most BDAs were chosen for intensive study in comparison with unrestored reference reaches. Monitoring focused on quantifying sediment volumes in BDA ponds and recording changes to stream stage and riparian groundwater. Despite differences in physical basin characteristics, BDA pools at both sites stored similar volumes of sediment and stored more sediment than reference pools. Sediment storage is positively correlated to BDA height and pool surface area. However, BDAs did not have a significant influence on shallow groundwater. The lack of groundwater response proximal to BDAs could indicate that local watershed factors have a stronger influence on groundwater response than restoration design 1 year post‐restoration. Systematic, long‐term studies of channel and floodplain response to BDAs are needed to better understand how BDAs will influence geomorphology and hydrology.